2014
DOI: 10.1039/c4ob00719k
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacteria from the Roseobacter clade produce sulfur volatiles via amino acid and dimethylsulfoniopropionate catabolism

Abstract: Dimethylsulfoniopropionate (DMSP) is a versatile sulfur source for the production of sulfur-containing secondary metabolites by marine bacteria from the Roseobacter clade. (34)S-labelled DMSP and cysteine, and several DMSP derivatives with modified S-alkyl groups were synthesised and used in feeding experiments that gave insights into the biosynthesis of sulfur volatiles from these bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…We tested the stress-protective properties of DMSP, its natural selenium analogue DMSeP (Ansede and Yoch, 1997;Ansede et al, 1999) and six synthetic DMSP derivatives (Dickschat et al, 2010;Brock et al, 2014) ( Fig. 1) for B. subtilis cells that were continuously challenged either by extremes in salinity (1.2 M NaCl) or growth temperatures (13°C and 52°C).…”
Section: Stress Protection By Dmsp and Its Derivatives Against High Smentioning
confidence: 99%
“…We tested the stress-protective properties of DMSP, its natural selenium analogue DMSeP (Ansede and Yoch, 1997;Ansede et al, 1999) and six synthetic DMSP derivatives (Dickschat et al, 2010;Brock et al, 2014) ( Fig. 1) for B. subtilis cells that were continuously challenged either by extremes in salinity (1.2 M NaCl) or growth temperatures (13°C and 52°C).…”
Section: Stress Protection By Dmsp and Its Derivatives Against High Smentioning
confidence: 99%
“…Va riation of GC conditions,columns,and floral extraction methods did not aid detection, thus indicating that the limitation is either suboptimal chromatographic properties for these compounds (broad peaks) or problems related to the specific antennal receptors.F urthermore,G C-MS screening for cyclohexane-1,3-dione-and pyrazine-based compounds known in other Australian orchid/thynnine wasp pollination systems, [2] as well as structurally related compounds,r evealed none of these compounds.Afinal set of semiochemical candidates was defined by their presence in both the active lateral sepal tips (clubs,F igure 1) and female wasp extracts,b ut not in the inactive floral remains.H igh-resolution GC-MS (GC-HRMS) revealed compounds with molecular formulae Them ass spectra and molecular formulae indicated that all four candidates were phenols with sulfur-containing substituents.T he identification process was expedited by the occurrence of the mass spectrum of our simplest candidate in the NIST-11 mass spectral library.T his compound (1;F igure 2), previously found in bacteria, [6] was confirmed by co-injection of the biological extracts with ac ommercially available reference compound. Based on similarities in molecular formulae and mass spectra, we proposed several structurally related compounds for the remaining three candidates,i ncluding hydroxy,hydroxymethyl and formyl compounds,which were all prepared synthetically and from which the matching compounds were successfully identified.…”
mentioning
confidence: 97%
“…[6] Other aromatic sulfurous compounds identified from plants or animals,apart from orchids,a re limited to thiophenes, [10] thiazoles, [11] and benzyl methyl sulfide (Figure 1). [12] Sulfurous floral volatiles are typically rare [13] and their function often unknown.…”
Section: Communicationsmentioning
confidence: 99%
“…[101][102][103] These compounds were easily prepared by the HCl catalysed Michael addition of dialkyl chalcogenides to acrylic acid (28). [101][102][103] These compounds were easily prepared by the HCl catalysed Michael addition of dialkyl chalcogenides to acrylic acid (28).…”
Section: Bacterial Conversion Of Dmsp Analogsmentioning
confidence: 99%
“…Interestingly, DMSeP was also efficiently demethylated, as indicated by the formation of various MeSeH derived volatiles, whereas no volatiles were detected from DMTeP. 103 Accordingly, the production of EtSH-derived volatiles from DESP could be observed, but was poor.…”
Section: Bacterial Conversion Of Dmsp Analogsmentioning
confidence: 99%